Towards Reducing Communication Gaps in Multicultural and Global Requirements Elicitation - Siakas, Errikos; Rahanu, Harjinder; Georgiadou, Elli; Siakas, Kerstin (Springer, 2021)
This paper focuses on the collaborative aspects of requirements elicitation, in the context of software, systems and service development. The aim is to identify and understand challenges of requirements elicitation in general and in distributed environments. We focus on human, social, and cultural factors that have an impact on communication in the requirements elicitation process. More specifically we aim to i) unfold potential cultural impediments that hamper the requirements elicitation process; ii) highlight cultural factors that should be taken into account in the requirements elicitation process in order to avoid incomplete and inconsistent requirements; and iii) make recommendations for alleviating the problems. In this paper our first step is to report on the findings of a review of the literature regarding culture in RE. The results suggest that the cultural studies in the field of RE are insufficient and thus more empirical studies are required. Secondly, we look at current solutions that are being adopted to assist in improving the cultural aspect of the requirements elicitation process. In the following step we map the identified communication gaps to the SPI Manifesto Values revealing the manifestations of the problems and finally we prescribe a set of recommendations that could be exercised and fulfilled by actors in the requirements elicitation process in order for them to improve cultural considerations in the RE process. These recommendations address the shortcomings that were identified in the literature review and mapped the Values of the SPI Manifesto. The proposals regard technologies, platforms, methods, and frameworks that are readily available. A requirements elicitation process that adopts one or a number of these proposals can help alleviate the challenges invoked by stakeholders’ cultural diversity in the RE process, thus leading to systems development and deployment that much better reflects the requirements/needs of diverse stakeholders and users.
Keywords: Requirements Elicitation; Culture; Global Software Development; fi=Tuotantotalous|en=Industrial Management|